Distribusi Frasa dalam Fabel Tradisional Berjudul "Sabuk Nabi Sulaiman" - Hua, Gloria Hanania Kinanthi Christ; Suhartono, Suhartono (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2025)
This study aims to analyze the distribution of phrases in the traditional fable titled Sabuk Nabi Sulaiman. The research employs a descriptive qualitative method with reading and note-taking techniques applied to the fable text. The collected data were analyzed based on the types of phrases in the Indonesian language, namely noun phrases, verb phrases, prepositional phrases, adjectival phrases, adverbial phrases, and numerical phrases. The results show that 63 sentences in the fable contain various types of phrases, consisting of 24 noun phrases, 24 verb phrases, 4 prepositional phrases, 8 adjectival phrases, 2 adverbial phrases, and 1 numerical phrase. Noun and verb phrases dominate the sentence structure, reflecting the story’s focus on describing characters, objects, and actions. Meanwhile, prepositional, adjectival, adverbial, and numerical phrases function as complements to provide additional information that enriches the context of the narrative. This research contributes to the advancement of education, particularly in teaching the Indonesian language. The findings can be utilized as instructional materials to understand sentence structures and phrase types in narrative texts. Additionally, this study expands insights into the linguistic richness of traditional fables, which can be leveraged as culturally-based teaching media. Thus, the results of this research are expected to assist educators and learners in better understanding and appreciating the Indonesian language in the context of traditional literature.